Electrical impedance tomography - Sim, Gerald Li Wei (2018)
Electrical Impedance Tomography is an imaging method that requires a stable current source to be able to be able to display a clear and precise image. There are many factors that affect the clarity and precision of the image. This experiment aims to improve the system by allowing it to produce images across a wide range of frequencies so as to be able to clearly detect tissue and other biological parts in a body. A water tank enclosed with probes was used to simulate an enclosed body. Different Op-Amps ranging from the TL071ACP, LM741 and AD844 op-amps were tested to produce a low current of 1mA across the water tank, with water used as the medium. The Enhanced Howland current source was used in this experiment, while the load is simulated with the tank containing water as the medium. The system was able to successfully simulate real-time Electrical Impedance imaging with accurate results and can be used for further research studies of EIT.